Klasterisasi Pelanggan Tenant Inkubator Bisnis STIKOM Bali Untuk Strategi Manajemen Relasi Dengan Menggunakan Fuzzy C-Means - I Gede Harsemadi; Dedy Panji Agustino; I Gede Bintang Arya Budaya (Jurnal Teknologi Informasi dan Multimedia, 2023)
Business Incubator is an institution that assists start-up businesses as their tenants that are still newly established or are growing. The main goal of a business incubator is to explore the most appropriate ways of assistance for tenants, from the process of starting a business, developing a business, and scaling up a business so that tenants can succeed in their business. Based on existing assistance data and the results of interviews with managers of the STIKOM Bali business incubator, one of the challenges for tenants is the ineffectiveness of the marketing process and strategic schemes in terms of maintaining customer loyalty. Ineffective and efficient plans can result in wasted use of resources. The customer relationship management (CRM) strategy can be applied by tenants as the solution, but the basis is that tenants need to know how to find out the right treatment for customers. So a strategy is needed to find out the characteristics of customers. In this case, it is done by using a business intelligence approach through customer clustering using fuzzy c-means. The dataset comes from the transaction of one of the tenants who is engaged in education technology. Based on values of the fuzzy partition coefficient (FCP) for the scenarios from clusters 2 to 10, it was found that 7 is the most optimal number of clusters (customer category) with the highest FCP value = 0.793. The main strategy that can be implemented based on tenant business for CRM is the pricing of subscription and engagement packages to customers regarding the information on both recently released and upcoming learning content.